Judicial Review and Constitutional Interpretation: The Development of the Role of the Indonesian Constitutional Court - Putra, Irman; Lubis, Arief Fahmi (West Science Law and Human Rights, 2023)
This research examines the role of Indonesia's Constitutional Court in constitutional review and interpretation, focusing on its development, key jurisprudential contributions, and the balance between judicial activism and restraint. Through a comprehensive analysis of landmark cases and scholarly literature, this research highlights the impact of the Constitutional Court on law and governance in Indonesia. The research reveals that while the Constitutional Court has demonstrated judicial activism by protecting fundamental rights and shaping the democratic process, it has also exercised restraint to maintain institutional balance and avoid political overreach. The Court's rulings on issues ranging from human rights to electoral law underscore its important role in upholding constitutional principles. However, the research also identified challenges relating to consistency, transparency and independence, which are critical to maintaining the Court's legitimacy and effectiveness. The findings suggest that the Court's ability to address these challenges will be critical to its future role in Indonesia's democratic framework.